Uterine Gαq/11 signaling, in a progesterone‐dependent manner, critically regulates the acquisition of uterine receptivity in the female mouse. Issue 8 (15th May 2019) - de Oliveira, Vanessa; Schaefer, Jennifer; Calder, Michele; Lydon, John P.; Demayo, Francesco J.; Bhattacharya, Moshmi; Radovick, Sally; Babwah, Andy V.
ABSTRACT: A nonreceptive uterus is a major cause of embryo implantation failure. This study examined the importance of the Gαq/11 ‐coupled class of GPCRs as regulators of uterine receptivity. Mice were created lacking uterine Gαq and Gα11 ; as a result, signaling by all uterine Gαq/11 ‐coupled receptors was disrupted. Reproductive profiling of the knockout females revealed that on d 4 of pregnancy, despite adequate serum progesterone (P4) levels and normal P4 receptor (PR) expression, there was no evidence of PR signaling. This resulted in the down‐regulation of heart and neural crest derivatives expressed 2, Kruppel‐like factor 15, and cyclin G1 and the subsequent persistent proliferation of the luminal epithelium. Aquaporin (Aqp) 11 was also potently down‐regulated, whereas Aηp5 /AQP5 expression persisted, resulting in the inhibition of luminal closure. Hypertrophy of the myometrial longitudinal muscle was also dramatically diminished, likely contributing to the observed implantation failure. Further analyses revealed that a major mechanism via which uterine Gαq/11 signaling induces PR signaling is through the transcriptional up‐regulation of leucine‐rich repeat‐containing GPCR 4 ( Lgr4 ). LGR4 was previously identified as a trigger of PR activation and signaling. Overall, this study establishes that Gαq/11 signaling, in a P4‐dependent manner, critically regulates the acquisition of uterine receptivity in the female mouse, and disruption of such signaling results in P4 resistance.—de Oliveira, V., Schaefer, J., Calder, M., Lydon, J. P., DeMayo, F. J., Bhattacharya, M., Radovick, S., Babwah, A. V. Uterine Gαq/11 signaling, in a progesterone‐dependent manner, critically regulates the acquisition of uterine receptivity in the female mouse. FASEB J. 33, 9374–9387 (2019). www.fasebj.org